Capacity Statement for Railways - Landex, Alex (Proceedings from the Annual Transport Conference at Aalborg University, 2007)
The subject “Railway capacity” is a combination of the capacity consumption and how the capacity is utilized. The capacity utilization of railways can be divided into 4 core elements: The number of trains, the average speed, the heterogeneity of the operation, and the stability. This article describes how the capacity consumption for railways can be worked out, and analytical measurements of how the capacity is utilized. Furthermore, the article describes how it is possible to state and visualize railway capacity. Having unused railway capacity is not always equal to be able to operate more trains. This is due to network effects in the railway system and due to the fact that more trains results in lower punctuality.